2016
DOI: 10.4018/ijskd.2016100102
|View full text |Cite
|
Sign up to set email alerts
|

Online Shopping Behavior

Abstract: Online shopping is a recent phenomenon in the field of E-Business with promising results indicating revolutionary change in shopping in the world. Accessibility and convenience are the key drivers for a major shift to online shopping. Due to ever increasing work pressure, multiple roles in life style, paucity of time, consumers are on the lookout of such facility that can suit to their changing needs. Online shopping provides the right solution to get the desired goods and services with a touch on the computer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Online shopping behavior is an individual's overall perception and evaluation of the product or services during shopping online, which could result in positive or negative feedback (Katta & Patro, 2016). Li and Zhang (2002) stated that online shopping behavior relates to a customer's psychological condition about the completion of the online buying process.…”
Section: Online Purchase Behaviormentioning
confidence: 99%
“…Online shopping behavior is an individual's overall perception and evaluation of the product or services during shopping online, which could result in positive or negative feedback (Katta & Patro, 2016). Li and Zhang (2002) stated that online shopping behavior relates to a customer's psychological condition about the completion of the online buying process.…”
Section: Online Purchase Behaviormentioning
confidence: 99%
“…However, the e-vendors adopt price rebates/ discounts as a means of promoting devices to attract more consumers (Erdoğmus & Çiçek, 2011). Katta and Patro (2016) identified that consumers focus on products with lower prices as they do not want to buy the products at a higher price. Baubonienė and Gulevičiūtė (2015) found that the facility to compare the competitive prices of similar products and purchase them at the cheapest price is the most valuable feature in the digital shopping context.…”
Section: Price Offeringsmentioning
confidence: 99%
“…Website factor was used as one part of the independent variable and measured with a 5-point Likert scale as used by (Katta & Patro, 2017;Clemes et al, 2014). The expression of views of respondents was accumulated with (1 = strongly disagree to 5 = strongly agree).…”
Section: The Modelmentioning
confidence: 99%